Angiospermic Parasites of our Forests - Mathur, Anand Kumar (Indian Forester, 1949)
Parasites are plants which depend on other plants (called ’Hosts’) for their total or partial requirements of food. Many flowering plants, besides a large number of Cryptogams, are known to exist as parasites and do considerable damage to our garden and forest plants. Loranthus is one such, and a number of species of this parasite are known to attack many of our fruit and timber trees, including teak, sal, oak, gumbhar, Wattles etc. It has heen noticed that a particular species of Loranthas attacks a particular plant, though this preferential treatment has not yet been established. Much more elaborate work on these lines requires to be done. No proper control and eradication methods of Loranthus are as yet known, except that of cutting the affected branch below the point of infection and burning it completely. Biological or any other method of control has not been tried (as in the case of Lantana, for example), though the problem has assumed considerable importance and requires more attention than paid to it at present. Many plantations raised at great cost had to be abandoned and written off due to its severe attack, as for example, the Gmelina plantations in Bengal and Burma and the Wattle plantations of South India. Reliable data of the expenditure incurred in the eradication of Loranthus by the cutting and burning method are not available.